2009
DOI: 10.1108/16605370910963518
|View full text |Cite
|
Sign up to set email alerts
|

Tourism expert perceptions for evaluating climate change impacts on the Euro‐Mediterranean tourism industry

Abstract: Purpose -The purpose of this paper is to analyse perceptions among European tourism experts specialising in tourism planning regarding the impact that climate change may have on tourism management. Design/methodology/approach -The methodology used was the double convergent Delphi Method. A total of 70 European experts in tourism planning were surveyed to determine their opinions. Two focus groups of experts were organised, first to fine-tune the questionnaire before implementing the Delphi method and, second, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 23 publications
2
14
0
2
Order By: Relevance
“…Studies with a diverse range of tourism stakeholders in 11 countries have found they were reasonably well informed about the potential impacts of climate change on tourism, but not highly concerned that the impacts would significantly affect their businesses 101,115,116,214–228. The large majority recognized the need for climate change adaptation and were highly optimistic about their capacity to overcome the challenges of climate change.…”
Section: Adaptation—is Tourism Prepared?mentioning
confidence: 99%
“…Studies with a diverse range of tourism stakeholders in 11 countries have found they were reasonably well informed about the potential impacts of climate change on tourism, but not highly concerned that the impacts would significantly affect their businesses 101,115,116,214–228. The large majority recognized the need for climate change adaptation and were highly optimistic about their capacity to overcome the challenges of climate change.…”
Section: Adaptation—is Tourism Prepared?mentioning
confidence: 99%
“…Ademais, o clima é um fator intrínseco a escolha de um DT, pois está associado à imagem do lugar (Goh, 2012), além de ser um elementochave ao estudo dos mercados turísticos (Eugenio-Martin y Campos-Soria, 2009). Essa afirmação pode ser confirmada ao considerar que as características climáticas condicionam o desenho dos calendários de férias, os quais podem ser associados a atividades de lazer, a sensação de segurança, relacionado aos efeitos da saúde, além de ser um elemento base ao bem-estar e satisfação do turista (Valls y Sardá, 2009). Entretanto, os fatores meteorológicos influenciam mais as viagens domésticas, pois as viagens internacionais tendem a ser planejadas com maior antecedência e ser menos sensíveis a estas mudanças (Otero-Giráldez, Álvarez-Díaz y González-Gómez, 2012).…”
Section: Fatores Físicosunclassified
“…Vale destacar que, em vista dos efeitos gerados pelos câmbios climáticos surge a necessidade de criar novas regulações para o setor, principalmente referentes ao uso de Investigaciones Turísticas N° 9, enero-junio 2015, 70-98 88 recursos e preservação ambiental (Valls y Sardá, 2009). Tsai y Chen (2010 e (Faulkner, 2000) pontuam particularmente a necessidade de instrumentos de previsão e planos de gestão para situações de risco, como nos casos de terremotos e outros desastres naturais.…”
Section: Fatores Institucionaisunclassified
“…Finally, both public and private stakeholders could be responsible for 79 promoting greater environmental awareness (Valls and Sardà, 2009) 80 about the impacts of tourism energy use by developing environmental 81 education campaigns about the optimization of energy consumption (e.g., 82…”
Section: Island 78mentioning
confidence: 99%
“…Consequently, the tourism industry may be affected (Valls & Sardà, 2009), making it a less sustainable activity not only environmentally but also economically (Perry, 2006). Hein et al (2009) estimated that current Spanish touristic volume could be reduced between 5 and 14% based on the current estimated temperature increase projections.…”
Section: Introductionmentioning
confidence: 99%